Transient elastography can stratify patients with Child–Pugh A cirrhosis according to risk of early decompensation. Issue 12 (December 2018) - Dillon, Audrey; Galvin, Zita; Sultan, Alyshah A.; Harman, David; Guha, Indra N.; Stewart, Stephen
Abstract : Background: Compensated cirrhosis has a variable prognosis depending on stage. There are currently no straightforward and robust tools in clinical practice to predict decompensation in Child–Pugh A cirrhosis. We set out to determine whether transient elastography (TE) could be used across liver disease aetiologies to determine risk of decompensation. Patients and methods: Participants were enrolled at two sites (Dublin and Nottingham) and followed up for a minimum of 2 years. The primary outcome of the study was liver decompensation, defined as the development of overt hepatic encephalopathy or ascites or presentation with bleeding varices. All patients received a TE examination to measure liver stiffness measurement (LSM) and had routine blood measurements taken at the baseline visit and on each subsequent visit. Results: In 259 participants, the overall rate of liver-related outcome was 31 per 1000 person-years (95% confidence interval: 19–47 per 1000 person-years). Of the total population, 6 and 11% developed a liver-related outcome within 2 and 4 years of follow-up, respectively. There were no events in the population with a LSM less than 21 kPa. A LSM of more than 35 kPa was associated with a decompensation risk of 39% at 4 years. For each unit increase in the LSM above 20 kPa, the risk of liver-related outcome increased by 6% (hazard ratio=1.06; 95% confidence interval: 1.04–1.82) after adjusting for age, sex Mayo End Liver Disease Score, cohort source and aetiology. Conclusion: The risk of liver decompensation increased with increasing LSM in mixed aetiology compensated cirrhosis. LSM may be used to risk stratify patients, potentially reassure patients with low scores, and select patients with higher scores for experimental therapeutic studies with acceptable timelines. Abstract : Supplemental Digital Content is available in the text.